2003
DOI: 10.1002/anie.200352564
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Dinuclear MnVO Complex and Its Efficient Evolution of O2 in the Presence of Water

Abstract: The oxidation of water in the process of dioxygen evolution is catalyzed by an oxygen-evolving complex (OEC) in photosynthesis, which is one of the most important and fundamental chemical processes in nature. [1][2][3] The active site in a photosynthetic OEC protein contains a tetramanganese cluster, [4] which adopts a Y-shaped geometry as revealed by recent X-ray structure analysis of photosystem II.[5] Though the mechanism of dioxygen evolution has not been determined, the stage of oxygen evolution would inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
218
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(225 citation statements)
references
References 35 publications
7
218
0
Order By: Relevance
“…Top: bis-porphyrin functional model for oxygen evolution (figure was reproduced from ref. [80], with permission of the copyright holders). Bottom: a proposed mechanism for biological oxygen evolution that closely resembles the proposed reactions of the bis-porphyrin complex (figure was reproduced from ref.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Top: bis-porphyrin functional model for oxygen evolution (figure was reproduced from ref. [80], with permission of the copyright holders). Bottom: a proposed mechanism for biological oxygen evolution that closely resembles the proposed reactions of the bis-porphyrin complex (figure was reproduced from ref.…”
Section: Discussionmentioning
confidence: 99%
“…However, ligand lability of Mn complexes can lead to instability of the catalyst under catalytic conditions, although Nature has overcome this problem of ligand lability by encapsulating the Mn ions in the OEC within the proteins of PSII. While instability is an issue for manganese model complexes, a number of successes have been reported [40,[79][80][81][82][83]. In this section, the manganese-based synthetic water-oxidation catalysts will be examined and their proposed mechanisms compared to the mechanisms proposed for the OEC.…”
Section: Manganese Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…41 Gao et al 46 very recently reported that a [Mn III -corrole] + complex can be converted into a Mn V -oxo complex which undergoes reductive elimination of oxygen on attack by hydroxide ion. An earlier study by Shimazaki et al 47 found that a dimanganese(III)-porphyrin dimer is oxidised by mchloroperbenzoic acid (mCPBA) to a dinuclear Mn V =O complex, which releases oxygen almost stoichiometrically on addition of acid. However, catalytic turnover was not demonstrated in these studies.…”
Section: Fig 2 Examples Of Ruthenium and Iridium Molecular Catalystsmentioning
confidence: 99%